Cars, conduits, and kampongs : the modernization of the Indonesian city, 1920-1960 - Colombijn, Freek; Coté, Joost; Colombijn, Freek, 1961- (Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde, 2014)
"Cars, Conduits and Kampongs offers a wide panorama of the modernization of the cities in Indonesia between 1920 and 1960. The contributions present a case for asserting that Indonesian cities were not merely the backdrop to processes of modernization and rising nationalism, but formed a causal factor. Modernization, urbanization, and decolonization were intrinsically linked. The various chapters deal with such innovations as the provision of medical treatments, fresh water and sanitation, the implementation of town planning and housing designs, and policies for coping with increased motorized traffic and industrialization. The contributors share a broad critique of the economic and political dimensions of colonialism, but remain alert to the agency of colonial subjects who respond, often critically, to a European modernity"--